Pengaruh Kualitas Sumber Daya Manusia dan Profesionalisme terhadap Kinerja Karyawan dengan Komitmen Organisasi sebagai Variabel Intervening (Studi Kasus pada Karyawan Dinas Pendidikan Hulu Sungai Selatan) - Gerhana, Wida; Rezti, Rezti; Wasis, Wasis (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2019)
This study is aimed to investigate the direct and indirect effect of the Quality of Human Resources, Work Professionalism and Organizational Commitment on Employee Performance at Dinas Pendidikan Hulu Sungai Selatan. This study approach is a quantitative approach. In this study, there are 27 employees as the population and they are taken as the sample by using census technique which the entire population is the same as the sample. The path analysis is used to analyze the data. The analysis result showed that the Quality of Human Resources and Work Professionalism have a direct effect on Employee Performance. Besides having a direct effect, the Quality of Human Resources and Work Professionalism also have an indirect effect on performance through Organizational Commitment.Simultaneously, the Quality of Human Resources, Work Professionalism and Organizational Commitment support the Employees Performance at Dinas Pendidikan Hulu Sungai Selatan.